Simulation-Based Study of Harmonic Distortion from EV Chargers in Low-Voltage Distribution Networks - Panjiyar, Anil Kumar; Aryal, Subrat; Yadav, Rashmi (Journal of Advanced College of Engineering and Management, 2025)
An electric utility must be able to handle to handle the energy demand as well as the peak demand brought on by EV charging because of the world’s growing use of electric vehicles. A utility must be able to keep its THD (use full form) within the specified range in addition to meeting peak demand and energy demands. Stated differently, the penetration of EVs into the power system has the potential to disrupt the system’s voltage and current waveforms. Therefore, we need to be able to make the supply side of the EV battery charging circuit harmonic free in order to maintain the system’s health. Either an active filter or a passive filter can be used for harmonic compensation. According to design, an active filter can remove any amount of harmonic content; however, it is more expensive. A passive filter with a clever design can be useful for eliminating a fixed harmonic component or specific harmonic content. In this project implementing the filter multiple EV chargers are simulated and the harmonic obtained in the supply side is studied. Both single phase and three phase chargers are simulated and the results analysed. The study uses MATLAB/SIMULINK software.